O conhecimento das funções e a formação dos auxiliares odontológicos atuantes no serviço público de saúde de municipios do noroeste paulista - Freire, Ana Carolina da Graça Fagundes [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Rovida, Tânia Adas Saliba [UNESP]; Garbin, Artênio José Isper [UNESP] (My University, 2011)
The aim of this study was to evaluate the knowledge of Hygienists (TSB) and Dental Auxiliaries (ASB) in relation to their roles regulated by Law number 11.889, December 24th, 2008, and formation of them and capacitating received before they had been admitted in public health system. It’s a transversal and descriptive study where the target population were TSB and ASB (N=76) that works in public service from 5 cities of the DRS II-SP. Data collection was performed by semi-structured instrument with opened and closed questions. The answer rate was 90.79% (n=69). The results showed that the majority of professional know part of their duties (56%) Near half of them had formation course (47.8%). In relation to information received during formation courses, 80% stated had received all information necessary to actualization of knowledge, however, 84% stated to feel necessity to actualize their knowledge to develop their works, 58% of professionals said that they don’t receive capacitating after they had been admitted. It was possible to conclude that the majority of professionals know part of their roles, has formation course and the majority don’t receive capacitating when they are admitted in public health system, however, it was observed that a part of them don’t have specific formation yet and don’t know part of their roles according to current legislation

Objetivo: Avaliar o conhecimento dos Técnicos em Saúde Bucal (TSB) e Auxiliar de Saúde Bucal (ASB) quanto à realização de suas funções regulamentadas pela Lei nº 11.889, de 24 de dezembro de 2008, assim como a formação desses profissionais e a capacitação recebida antes de exercerem suas funções no sistema público de saúde. Metodologia: Trata-se de um estudo transversal descritivo em que a população-alvo foram os TSB e ASB (N=76) que atuam no sistema público de cinco municípios da área de abrangência do DRS II-SP. A coleta dos dados foi realizada por meio de questionários semiestruturados e autoadministrados, com perguntas abertas e fechadas. A taxa resposta foi de 90,79% (n= 69). Resultados: Os resultados mostraram que a maioria dos profissionais conhece parte de suas funções (56%). Quase metade dos profissionais relatou ter curso de formação (47,8%). Quanto às informações recebidas nos cursos técnicos frequentados, 80% afirmam ter recebido todas as informações necessárias para sua formação, no entanto 84% relatam sentir necessidade de atualização de seus conhecimentos para o desenvolvimento de suas atividades e 58% dos profissionais declararam não receber capacitação após a contratação. Conclusão: Conclui-se, portanto, que a maioria dos profissionais conhece parte de suas funções, tem curso de formação e a grande parte deles não recebe capacitação quando ingressam no sistema público de saúde. Observou-se que uma parcela considerável ainda não possui formação específica, desconhecendo parte de suas funções previstas em legislação vigente.
Knowledge of the roles and training of dental assistants who perform their duties in public health services to municipalities in the northwest region
Keywords: Dental staff; Inservice training; Public service; Recursos humanos em Odontologia; Capacitação em serviço; Serviço público